HUMAN CAPITAL DEVELOPMENT AND ECONOMIC GROWTH IN NIGERIA - *, Ogunleye; , Owolabi, O. O.; Sanyaolu, O. A.,; Sanyaolu, O. A.,; A, O.; O, O. (IJRDO - Journal of Business Management, 2017)
This study employs the ordinary least square regression analysis to examine the impact of human capital development on economic growth of Nigeria, using annual time series date from 1981 to 2015. The empirical results show that human capital development has significant impact on economic growth, as proxy by the gross domestic product. In line with theory, the human capital development indicators namely secondary school enrolment, tertiary school enrolment, total government expenditure on health and total government expenditure on education exhibit positive and statistically significant impact on economic growth of Nigeria which implies that these indicators are indispensable in the achievement of growth in the Nigerian economy. However, life expectancy and primary school enrolment exhibit a negative and statistically insignificant impact on economic growth of Nigeria. The study concluded that the Nigerian government should ensure to allocate adequate resources for the development of human capital in order to enhance economic growth in Nigeria. The study also recommended that going forward the government and policy makers should increase its total expenditure on education, ensure sufficient budgetary allocation on health expenditure, and ensure a standard is set across all secondary and tertiary institutions in the country so that proper human capital required for any individual to become productive and economic growth is enhanced.